ANALISA DAN PERANCANGAN BOLT INVENTORY MANAJEMENT SYSTEM : PT. INTERNUX - Fitri Herawati; Yaya Sudarya Triana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
PT. Intenux is a business entity the results of cooperation between PT Firstmedia, Tbk with the largest investment and trading company in Japan & Mitsui Co., Ltd. As for the problems that occur on systems that are running currently pengelohan i.e. for incoming and outgoing goods data between the warehouse and the warehouse, shipping data center that is still on the record into the big book in accordance with the letter or letters the submission or request goods only in noted in a piece of paper and then copy it back to your new computer by admin section of the warehouse. So sometimes experience difficulties in information provided does not correspond to an existing item availability. The purpose of this study is to analyze and design an information system inventory management item, by using UML as Use Case diagrams, Sequence Diagrams, and Class diagrams. who can manage the entire activity out of incoming goods, stock items and reports. Information systems will be analyzed and designed is expected to tackle the whole problem has been in describe.